KONSEP DIRI DAN ORIENTASI MASA DEPAN PADA SISWA SYZYGY DI BANDA ACEH - Khairi Wahyuna; Nurhasanah Nurhasanah; Abu Bakar (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2018)
The issue of sexual orientation in adolescents often worries parents, edocators, government and others. How to form a positive self concept so as to have a picture of a good future in accordance with their respective gender. This research aim to know self concept and future orientation of syzygy student in banda aceh. This research use descriptive qualitative approach. The subjects of this study are students whu classified syzygy (aanimma animus) as many as 5 people high school category. While the object of this research is the concept of self and future orientation. Data colection is done by interview.the self concept of syzygy students is viewed from the perspective of physically and non physically, and future orientation is seen fromhow desire to shape life in the future. Positive and negative self concept that they have affect the design of their futuere. At first glance looks like LGBT even there is a sexual orientation that has diverged. Therefore, in relation to counseling service, teachers are expected to provide extensive and in-depth guidance on self-conceptual materials and future orientations specific to syzygy student (anima animus), so that their existing sexual orientation does not fall into the things that are not desirable and that are not in accordance with the norms of life.